1989
DOI: 10.1001/archpedi.1989.02150220142035
|View full text |Cite
|
Sign up to set email alerts
|

School Breakfast Program and School Performance

Abstract: Children who participate in the School Breakfast Program show significant improvement in academic performance and tardiness rates, and a trend toward improvement in absenteeism. The School Breakfast Program was created by Congress in 1966 to provide a breakfast on school days for low income children who would otherwise have none. Children (N=1,023) in grades 3, 4, 5, and 6 in six elementary schools in Lawrence, Massachusetts, were chosen for a one-year study on the effects of Breakfast Program participation. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 16 publications
4
89
0
3
Order By: Relevance
“…18 A study among low-income elementary school students indicated that those who participated in the school breakfast program had greater improvements in standardized test scores and reduced rates of absenteeism and tiredness compared to children who qualified for the program but did not participate in the school breakfast program. 19 Other dietary habit observed in the present report were taking meals outside the home, infrequent intake of fruits and vegetables and snacking. These have been similarly documented, namely: eating out of the home and skipping meals.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…18 A study among low-income elementary school students indicated that those who participated in the school breakfast program had greater improvements in standardized test scores and reduced rates of absenteeism and tiredness compared to children who qualified for the program but did not participate in the school breakfast program. 19 Other dietary habit observed in the present report were taking meals outside the home, infrequent intake of fruits and vegetables and snacking. These have been similarly documented, namely: eating out of the home and skipping meals.…”
Section: Discussionsupporting
confidence: 47%
“…6 The detrimental consequence of poor dietary habits such as skipping breakfast has been reported by Pollitt et al 18 and Meyers et al 19 and these include increasing prevalence of poor academic performance on standardized tests, absenteeism and tiredness among those who skipped breakfast when compared with those who always ate breakfast.…”
Section: Discussionmentioning
confidence: 98%
“…[38][39][40] Children attending schools with school nutrition programs have improved scores on standardized academic tests. 41 Home visiting by nurses has been shown consistently to reduce rates of childhood injury, to increase fathers' involvement, to reduce family welfare dependency, and to improve school readiness. 42 Housing subsidies have resulted in improved neighborhood safety and reduced exposure to violence.…”
Section: How Can Schools and Communities Promote School Readiness?mentioning
confidence: 99%
“…There is some evidence that school feeding programes improve children's cognition and school achievement (Meyers et al, 1989;Powell et al, 1983;Chandler et al, 1995;Jacoby et al, 1996).…”
Section: Introductionmentioning
confidence: 99%